Productino of KSR-III Airglow Photometers to Measure MUV Airglows of the Upper Atmosphere Above the Korean Peninsular - T. H. Oh; K. C. Park; Y. H. Kim; Y. Yi; J. Kim (Journal of Astronomy and Space Sciences, 2002)
We have constructed two flight models of airglow photometer system (AGP) to be onboard Korea Sounding Rocket-III (KSR-III) for detection of MUV dayglow above the Korean peninsular. The AGP system is designed to detect dayglow emissions of OI 2972 Å, N_2 VK (0,6) 2780Å, N_2 2PG 3150Å and background 3070Å toward the horizon at altitudes between 100 km and 300 km. The AGP system consists of a photometer body, a baffle, an electronic control unit and a battery unit. The MUV dayglow emissions enter through a narrow band interference filter and focusing lens of the photometer, which contains an ultraviolet sensitive photomultiplier tube. The photometer is equipped with an in-flight calibration light source on a circular plane that will rotate at the rocket's apogee. A baffle tube is installed at the entry of the photometer in order to block strong scattering lights from the lower atmosphere. We have carried out laboratory measurements of sensitivity and in-flight calibration light source for the AGP flight models. Although absolute sensitivities of the AGP flight models could not be determined in the country, relative sensitivities among channels are well measured so that observation data during rocket flight in the future can be analyzed with confidence.